THE INFLUENCE OF ONLINE PROMOTIONS AND PRICE PERCEPTIONS ON THE PURCHASING DECISIONS OF MS GLOW USERS AT UNIVERSITY OF MUHAMMADIYAH TANGERANG - Priyatna, Eka Hendra; Rahmawati, Dewi; Kusdianto, Kusdianto (Universitas Muhammadiyah Tangerang, 2024)
This research aims to analyze the influence of online promotion factors (X1) and price perception (X2) on purchasing decisions (Y) on MS Glow products. This research is quantitative research and survey research. The sample taken in this research was 100 respondents. Data obtained from distributing questionnaires. Primary data processing uses MS.Excel and Statistical Package For Social Science (SPSS) version 26 as evaluation. Meanwhile, the data analysis used in this research includes descriptive statistical analysis, data quality testing, classical assumption testing, linear regression analysis, correlation testing, coefficient of determination testing and hypothesis testing. The results of this research show that the variables Online Promotion Factor (X1) and Price Perception Factor (X2) simultaneously have a positive and significant effect on Purchasing Decisions (Y) as indicated by the Fcount>Ftable value, namely 120.505 > 3.09 with a significant value of 0.000 < 0.05.